PARTISIPASI E-COMMERCE DI INDONESIA: KAJIAN PENGARUH FAKTOR KEPERCAYAAN, RISIKO, MANFAAT DAN KUALITAS WEBSITE - Ahmad Syafaat; Arief Budiman; Akhmad Supriyanto (Universitas Lambung Mangkurat, 2017)
This research aims to find out and analyze the influence among trust (X1), perceived risk (X2), perceived benefit (X3) and website quality (X4) as independent variables simultaneously toward e-commerce participation (Y) in Indonesia. The Method of this research used online questionnaire with sample 258 respondents. The variables measurement uses Likert’s Scale technique weighting scale from 1 to 5. To find out the relation between independent and dependent variables and regression weight between indicator and laten variable are used statistical technique Structural Equation Model (SEM) with AMOS 21 program. The result of research concludes that there is a positive significant influence from trust, perceived benefit and website quality variables toward participation variable and a negative significant influence from perceived risk variables toward participation. From the four independent variables, the highest percentage (35,3%) is website quality variable.